What is the Motivation of Travellers? An investigation of quotes on TripAdvisor’s facebook page - Binbasioglu, Hulisi (2019)
The online review websites such as TripAdvisor provide the advantages to access this information. If these websites post the reviews on their social media addresses, it is possible to spread the information more. Travellers have also the opportunity to disseminate their motivations and experiences about their travel on social media and online review websites. Content analysis method was applied to understand TripAdvisor travellers’ motivation. The findings of this study suggest that novelty/adventure and knowledge/intellectual are two major travel motivations among TripAdvisor travellers. The findings of the current study are important for both tourism managers and academicians to better understand travel motivation of people on social media. It is expected that the results of this study help tourism businesses and destinations to understand travellers’ opinions and enhances their awareness of customer needs. Thus, they can easily adapt their marketing strategies. No research has been done on examining the motivation of TripAdvisor travellers regarding their quotes on Facebook. Thus, the current study contributes to an understanding of the factors that influence peoples’ travel motivation.